The pharmacokinetics of cell-penetrating peptides - Sarko, Dikran; Beijer, Barbro; Garcia Boy, Regine; Nothelfer, Eva-Maria; Leotta, Karin; Eisenhut, Michael; Altmann, Annette; Haberkorn, Uwe; Mier, Walter (Molecular pharmaceutics, 2010)
Cell-penetrating peptides (CPPs) are able to penetrate the cell membrane carrying cargoes such as peptides, proteins, oligonucleotides, siRNAs, radioisotopes, liposomes, and nanoparticles. Consequently, many delivery approaches have been developed to use CPPs as tools for drug delivery. However, until now a systematic analysis of their in vivo properties including potential tumor binding specificity for drug targeting purposes has not been conducted. Ten of the most commonly applied CPPs were obtained by solid phase peptide synthesis and labeled with 111In or 68Ga. Uptake studies were conducted using a panel of six tumor cell lines of different origin. The stability of the peptides was examined in human serum. Biodistribution experiments were conducted in nude mice bearing human prostate carcinoma. Finally, positron emission tomography (PET) measurements were performed in male Wistar rats. The in vitro uptake studies revealed high cellular uptake values, but no specificity toward any of the cell lines. The biodistribution in PC-3 tumor-bearing nude mice showed a high transient accumulation in well-perfused organs and a rapid clearance from the blood. All of the CPPs revealed a relatively low accumulation rate in the brain. The highest uptake values were observed in the liver (with a maximal uptake of 51 %ID/g observed for oligoarginine (R9)) and the kidneys (with a maximal uptake of 94 %ID/g observed for NLS). The uptake values in the PC-3 tumor were low at all time points, indicating a lack of tumor specific accumulation for all peptides studied. A micro-PET imaging study with 68Ga-labeled penetratin, Tat and transportan10 (TP10) confirmed the organ distribution data. These data reveal that CPPs do not show evidence for application in tumor targeting purposes in vivo. However, CPPs readily penetrate into most organs and show rapid clearance from the circulation. The high uptake rates observed in vitro and the relatively low specificity in vivo imply that CPPs would be better suited for topical application in combination with cargoes which show passive targeting and dominate the pharmacokinetic behavior. In conclusion, CPPs are suitable as drug carriers for in vivo application provided that their pharmacokinetic properties are also considered in design of CPP drug delivery systems.
Gesehen am 07.08.2023